A Novel Image Edges Detection by Using Gaussian Functions - Khaleaf, Hussain K.; Kamarul Hawari, Ghazali; Ajisman, Apen (Universiti Malaysia Pahang, 2013)
Nowadays, the Edge detection is a very important process and treatments in biomedical image's application to the understanding and analysis of distinction objects in digital images. Edge detection is discontinuity or sudden change process of certain visual properties (such as the intensity of lighting, composition, color). In this study, edge detected of digital color images using a Gaussian function was proposed. First, the least squares' method used to compress the image data. Second, color image edge detected by using Sobel's operator by changing the intensity of homogeneous regions. Finally, the result shows the effectiveness and capability of the proposed to detect the real edges in color photographs with different color compared with standard methods to detect the edge.